Assessment of learning outcomes : cognitive domain : book 1 - Gutierrez, Danilo S. (Malabon City, Philippines : Kerusso Publishing House, 2007)
This book is the first of the two- volume series designed to help students and teachers measure and evaluate learning outcomes in the cognitive domain, Book II is about assessment of learning outcomes in psychomotor and affective domains.
Chapter 1. The Nature of educational assessment -- Chapter 2. Instructional objectives and learning outcomes -- Chapter 3. Approaches and trends in educational assessment -- Chapter 4. Preparing for assessment -- Chapter 5. Writing multiple- choice items -- Chapter 6.Writing true- false and matching items -- Chapter 7. Writing short answer and essay -- Chapter 8. Characteristics of a good test -- Chapter 9. Improving the test items -- Chapter 10. From discrete- point to integrative assessment -- Chapter 11. Measures of central tendency -- Chapter 12. The Measures of variability and position -- Chapter 13. Interpretation of test scores -- Chapter 14. Correlating two variables -- Chapter 15. Marks and learning outcomes -- Chapter 16. Evaluating assessment plants and devices.
Keywords: LEARNING OUTCOMES -- ASSESSMENT